2023
DOI: 10.21203/rs.3.rs-2525359/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of FIFA 11+ warm-up program on kinematics and proprioception in adolescent male and female soccer players; a parallel‑group randomized control trial

Abstract: This study aimed to compare the effects of 8 weeks 11+ warm-up injury prevention program on kinematics and proprioception in adolescent male and female soccer players. forty adolescent soccer players (20 males, 20 females) aged between 14-16 years old were randomly assigned into four groups. The experimental group performed the 11+ program for 8 weeks and the control group did their warm-up program. The kinematic variable in a cutting maneuver was measured using VICON motion analysis and ankle and knees’ prop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In their research, Sidi et al (2023) examined the effect of an eight-week FIFA 11 + training program on knee kinematics and proprioception of male and female soccer players. The results of this research indicated that knee proprioception and valgus angle improved after applying the exercise protocol [24]. The similarity of training research's program this the current research can may be one of the reasons for its alignment.…”
Section: Discussionmentioning
confidence: 54%
“…In their research, Sidi et al (2023) examined the effect of an eight-week FIFA 11 + training program on knee kinematics and proprioception of male and female soccer players. The results of this research indicated that knee proprioception and valgus angle improved after applying the exercise protocol [24]. The similarity of training research's program this the current research can may be one of the reasons for its alignment.…”
Section: Discussionmentioning
confidence: 54%
“…Prior research has found flexibility, proprioception, and kinematics to also be important factors when evaluating lower extremity injuries. [59][60][61] CONCLUSIONS NCAA men's and women's soccer players had different hip strength profiles that fit their gender-specific injury patterns. Men's NCAA soccer players tend to have higher rates of hip and groin strains, and men in our cohort had strength ratios that were deficient in the hip flexors and adductors compared with women.…”
Section: Limitationsmentioning
confidence: 99%
“…Previous studies have shown that the programme can reduce injury risk in football players 5–7. The injury preventive effect of the 11+ programme is likely to be twofold: (1) an acute increase in physical and mental preparedness8 and (2) a long-term effect of the strength and proprioceptive training programme, that is, players becoming stronger over time 9 10…”
Section: Introductionmentioning
confidence: 99%